Intergenerational Mobility of Housework Time in the United Kingdom - J. Ignacio Gimenez-Nadal; José Alberto Molina; Yu Zhu (Institute for the Study of Labor (IZA), 2014)
This paper analyzes the relationship between parents' time devoted to housework and the time devoted to housework by their children. Using data from the Multinational Time Use Study for the UK, we find positive intergenerational correlations in housework for both parents, indicating that the more time parents devote to housework, the more time their children will devote to housework. However, when endogeneity of the uses of time are considered using the British Household Panel Survey, we find that only fathers' housework time appears to have a statistically significant effect. The IV estimates fully support the FE estimates and suggest that father's housework induced by his partner's non-traditional gender role attitudes towards domestic division of labour and her actual labour supply in the previous wave, has a large and significant effect on children's housework time. Our results contribute to the field of intergenerational mobility of behaviors.
Keywords: J16; J22; 330; housework; household; intergenerational transfers; Multinational Time Use Study; British Household Panel Survey